PENGARUH PENGALAMAN MEREK, KEPERCAYAAN DAN KEPUASAN DALAM MEMBANGUN LOYALITAS MEREK PADA BRAND SEPATU LOKAL DI KALANGAN MAHASISWA - Mario Eko Prasetyo; Anton Agus Setyawan (Universitas Sarjanawiyata Tamansiswa, 2026)
This study seeks to investigate the roles of brand experience and brand trust as predictors of consumer satisfaction, while simultaneously examining their strategic implications for fostering brand loyalty toward domestic footwear brands within the student segment. This study employs a quantitative methodology with a causal associative model, operated through a series of statistical hypothesis tests. The research population consisted of active university students aged 18–35 years who had purchased and used Indonesian local footwear brands within the last six months. Purposive sampling was applied to ensure the relevance of respondents to the research objectives. Data collection was conducted through the distribution of a structured questionnaire adopting a five-point Likert scale, while data processing utilized inferential statistical techniques. The findings reveal that brand experience has a positive and significant effect on customer satisfaction, while brand trust also significantly enhances customer satisfaction. Furthermore, customer satisfaction is proven to have a positive and significant influence on brand loyalty, indicating that satisfaction plays a crucial role in fostering long-term consumer commitment to local footwear brands. These results highlight the strategic importance for local footwear businesses to consistently strengthen brand experience and trust in order to enhance customer satisfaction and ultimately build sustainable brand loyalty, particularly within the student segment as a promising market